Bioplastic Based on Starch from Keciri Tuber (Amorphophallus campanulatus) - Riskayanti, Yunita; Dilatais, Bunga Zorra; Natasya, Ditha; Nurhidayatullah, Nurhidayatullah (Jurnal Pijar Mipa, 2025)
Plastic waste is one of the primary contributors to environmental problems. In West Sumbawa Regency, particularly in Seteluk District, the use of plastic remains relatively high, as observed in schools and residential areas, including the researcher’s own environment. This is evidenced by the significant accumulation of plastic waste. The purpose of this study is to examine the potential of the keciri plant (Amorphophallus campanulatus) in West Sumbawa Regency, to analyze the characteristics of bioplastic made from keciri tuber starch (Amorphophallus campanulatus), and to determine whether keciri tuber starch (Amorphophallus campanulatus) can be utilized as a material for bioplastic production. The research method used in this study was experimental, employing a quantitative descriptive experimental design. The conclusions of the study are as follows: the keciri plant (Amorphophallus campanulatus) grows abundantly in the wild around the researcher’s residence, and it was also commonly found in other areas such as Poto Tano District, Seteluk District, and the villages of Senayan, Rempe, and Meraran. Based on data from three bioplastic tests conducted, the water resistance tests showed that all types of bioplastics exhibited similar water resistance levels, with an average of 60%. The biodegradability tests revealed that all types of bioplastics degraded completely within 5 days, indicating that the produced bioplastics are fully biodegradable in soil. For organoleptic tests, each type of bioplastic yielded different results. Bioplastics made with cooking oil and glycerol achieved the highest scores, followed by those made with VCO (virgin coconut oil) and no plasticizer, while those using coconut oil plasticizer scored the lowest. Since the researcher aimed to produce edible bioplastics, VCO was chosen as the plasticizer. Therefore, keciri tuber starch could be used for bioplastic production by mixing it with VCO plasticizer and pomelo juice extract, making it suitable for use as food packaging.